2015
DOI: 10.1017/jmo.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Exploring managers’ conceptions of wisdom as management practice

Abstract: This paper reports on an exploratory investigation into the concept of managerial wisdom. Six senior managers from diverse and large organisations in New Zealand were interviewed about their conception of managerial wisdom. The findings show that senior managers have a practical and positive conception of wisdom consisting of four factors: experience and knowledge, emotional intelligence, mentorship, and deliberation and consultation. The findings show that concepts of ‘spirituality’, ‘religiosity’, and, perha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…In fact, engaging in these questionable accounting practices is precisely why former Enron executives, such as Jeffrey Skilling, is serving a 24-year sentence. In a study of managerial wisdom, Alammar and Pauleen (2016) found that senior managers never addressed ethics. They related this to a possible agency theoretic position and concern that managerial wisdom does not include an ethics component.…”
Section: Toward Agent and Steward Predictionsmentioning
confidence: 99%
“…In fact, engaging in these questionable accounting practices is precisely why former Enron executives, such as Jeffrey Skilling, is serving a 24-year sentence. In a study of managerial wisdom, Alammar and Pauleen (2016) found that senior managers never addressed ethics. They related this to a possible agency theoretic position and concern that managerial wisdom does not include an ethics component.…”
Section: Toward Agent and Steward Predictionsmentioning
confidence: 99%
“…(Its main representative is the balance theory of wisdom (Sternberg 1998), but other representatives include Clayton and Birren, Holliday and Chandler, Orwoll and Perlmutter, and Sowarka. See Alammar and Pauleen (2016) and Sternberg (1998, pp. 348-349).)…”
Section: Practical Wisdom and Moral Psychologymentioning
confidence: 99%
“…(Other theories here span dominant personality research work (e.g., Bandura 1989;Deci and Ryan 2013;McAdams and St Aubin 1998;Ryan and Lynch 1989;Ryan and Deci 2006), post-modern constructivism (Gergen 1999(Gergen , 2011, and neo-Piagetian traditions of adult development theory (Alexander and Langer 1990;Cook-Greuter 1999;Kegan 1994;Loevinger 1966Loevinger , 1976 with an emphasis on postformal cognitivist dialectical thought.) Alammar and Pauleen (2016) identify a third school of thought that explores the correlation between personal traitssuch as gender, age, occupation, etc.and wisdom, i.e., identifying wisdom as a property of the person that integrates cognitive, reflective, and affective characteristics (Alammar and Pauleen 2016, p. 551).…”
Section: Practical Wisdom and Moral Psychologymentioning
confidence: 99%
“…Following were proposals for using the utility of agency theory to explain training and development outcomes (Azevedo & Akdere, 2008, 2010, 2011; Li & Huang, 2011). The empirical studies conducted and published within the HRD-related literature identified in this review described the limitations of their studies to application to the case and sample studied due to the sample size or specificity of the participants and respondents (Alammar & Pauleen, 2015; Blakeley & Higgs, 2014; Glick, 2011; Liu, Valenti, & Chen, 2016; O’Reilly, Doerr, Caldwell, & Chatman, 2014; Petrescu & Simmons, 2008; Rusaw & Rusaw, 2008; Singh, 2003). Research and practice related to testing and applying the principal–agent relationship are presented later in this article as implications for HRD.…”
Section: Agency Theory In Hrd-related Literaturementioning
confidence: 99%
“…Similar to trust is reputation. It is expected that reputation and wisdom will influence the principal’s influence in the principal–agent relationship (Alammar & Pauleen, 2015; Kolodinsky & Bierly, 2013); however, this is expected and needs to be verified. In contrast to trust is conflict.…”
Section: Implications For Hrdmentioning
confidence: 99%